Project scope optimization model and method on criteria profit, time, cost, quality, risk. Integrating Project Management Standards - Kononenko, Igor; Fadeyev, Valeriy; Kolisnyk, Mariia (Elsevier Ltd., 2012)
The paper presents a mathematical model of the structural optimization of the project scope, which includes five objective functions. One of the functions reflects the profit for the entire project life cycle. The others reflect the time of its realization, the cost of the project, the value of the generalized indicator of project product quality and the risk assessment associated with the project. The model takes into account the restrictions on the lack of financial debt after each phase completion, the duration of the project, the quality of the separate stages products. It is assumed that the project scope is given in the form of a network model with the alternatives of the work execution. The suggested model is a multi-objective, dynamic, containing Boolean variables, algorithmic and analytical objective functions and constraints. A method of multi-objective structural optimization of the project scope with constraints was proposed to solve the problem.
Keywords: project; scope; multy-objective optimization; network model; dynamic problem